Analisa Kebutuhan Dan Manajemen Pemeliharaan Elevator Pada Gedung Perum Perhutani Unit I Jawa Tengah - Aisyah Fitri Afifah; Tyas Herlintang P; Dianita Ratna K; Nugroho Hartono (Politeknik Negeri Semarang, 2017)
User-storey building in the activity from one floor to another floor of a multistory building need of vertical transportation (elevators). Elevator or lift is a vertical transportation used to transport people or goods. Elevators are generally used in the high rise buildings, typically more than three or four floors. Elevator specifications determined by the capacity, speed and carrying capacity. Selection is based on the use of elevators in the building people traffic, travel time back (round trip times), the peak time of use (peak-up times) and the waiting time in terms of capacity (handling capacity), the speed of the elevator. Adequate quantity for vertical transportation is an important factor, as it will affect the quality of service in a building, so we need a maintenance management that can manage performance elevators. Good elevator maintenance management includes periodic maintenance, checking the components, replacement of components that need to be replaced and the estimated cost of maintenance that is necessary to issue any annually building management. In Semarang city there are plenty of high rise office buildings, one of which is Perum Perhutani Unit I Central Java. The building has seven floors are used for the activities of the members. The method used in this research namely direct observation, primary and secondary data collection and data processing. From the results of data processing it can be concluded that the number of elevators in the building needs Perum Perhutani Unit I Central Java should totaling 3 units, while currently only available 2 units. In addition, the elevator maintenance management obtained regularly presented in the form of a checklist and budget maintenance costs as well as the replacement of some damaged components.Kata Kunci : elevator, kebutuhan, pemeliharaan